Introduction to Deep Learning - Ketkar, Nikhil (Deep Learning with Python, 2017)
This chapter provides a broad overview and an historical context on the subject of deep learning. It also gives the reader a roadmap for navigating the book, its prerequisites, and further reading to dive deeper into the subject matter.